A construção da realidade moderna: por uma heurística do controle na modernidade - Marcantonio, Jonathan Hernandes (2011)
The present work aims showing the Modernity as na available control structure presented during a whole historical and social process fulfilled of peculiar social and historical movements.Such study starts from three diferent, bu mainly frameworks, whose are: The theoretical appeal, the social/economical appeal and the institutional apeal. The reason of the present study is precisely de intent to show the control as na element which is present during the hole modernity period, til now a days. And, as long as these elements of control, anyone of them, exists, also will exist the Modernity itself, which throws off the possibility of the possibility of a new historical and/or social period discourse